Financing to Deposit Ratio (FDR) Sebagai Intervening Variabel Terhadap Profitabilitas: Evidance Dari Bank Umum Syariah Tahun 2016-2019 - Hendrianto, Hendrianto (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to prove empirically the effect of Net Performance Loan, Revenue Sharing on Return on Assets (ROA). The population in this study are 13 Islamic commercial banks that have been registered at IDX in 2016-2019. The sample was determined by using the porposive sampling method so that 54 samples were obtained. The data used is secondary data obtained from the IDX gallery. The hypothesis in this study was tested using path analysis to determine the direct and indirect effects of the independent variables used on the dependent variable. The results of this study indicate that partially BOPO has a significant effect on FDR, while ROA proxied by ROA has an insignificant effect on income. CAR has a significant effect on FDR, while CAR proxied by ROA has an insignificant effect on Revenue. FDR proxied by ROA has no significant effect on Revenue. NPF has no effect on FDR, while NPF as proxied by ROA has a significant effect on Revenue.